Experiments of Pulse-Shape Discrimination Technique of Alpha- and Beta (X, gamma)-Particles with Uses of a Phoswich and a CsI(Tl) Scintillation Detectors - Takao Tojo; Muhammad Zainuddin; Widodo Soemadi (Widyanuklida, 2000)
ABSTRACT A phoswich or sandwich-type scintillation detector consisted of a thin layer of ZnS(Ag) and a plate of NE 102A plastic scintillator and a single crystal-type CsI(Tl) scintillation detector have been applied to differentiate alpha- and beta (X, gamma)- particles by means of pulse shape discrimination (PSD) technique. In this experiment, rise time distributions of alpha- and beta-particles have been measured with uses of a couple of sources of 241Am and 90Sr (90Y) and a 93.3% enriched uranium-aluminum alloy. Rise time resolution of the PSD spectrometer has been measured as 8.8ns ± 1.2% in terms of FWHM (FWTM: l6.3ns), which has been measured with a pulse generator. The most probable rise times of ZnS(Ag)/NE 102A detector have been obtained as 1.473µs ± 0.3% with the FWHM of 40ns for alpha-particles (ZnS(Ag)) and as 32.2ns ± 4.8% with the FWHM of 18ns for beta (X, gamma)-particles (NE l02A). The most probable rise time of the CsI(Tl) detector has been determined as 1.288µs ± 0.l% with the FWHM of 54ns for alpha-particles and as 1.435µs ± 0.l% with the FWHM of 44ns for beta (X, gamma)-particles. It has been clarified that the PSD system equipped with the ZnS(Ag)/NE 102A and the CsI(Tl) detectors gives clearly differentiated count rates and spectra of alpha- and beta (X, gamma)-particles, and application of the PSD system to, for example, screening-out of the radwastes contaminated with alpha-emitters is expected to be very effective.